Climate Change and Agrobiodiversity - Cardozo Conde, Carlos Iván (Revista Colombiana de Investigaciones Agroindustriales, 2014)
One of humanities major challenges is to ensure global food security. Since the 60’s efforts have been made to increase food production for a growing population. Breeding programs have been playing an important role, as well as the communities of medium and small farmers who retain a high percentage of genetic variability of major crops through local production systems. New technologies have been incorporated such as biotechnology, eco-efficient agriculture, and intelligent agriculture to develop sustainable production systems. While the food supply has increased, the phenomena of global warming- GW and climate change -CC appear as a threat, because of its effects on phenological and physiological aspects of crops, estimated by modeling, forecasting a strong reduction in biodiversity and crop yields worldwide with regional variations. As far as these concerns, it’s necessary to make well-timed adaptation plans consistent with the vulnerability levels in different countries. In this situation,a strategy to adapt to future scenarios posed by GW; is to incorporate the most biodiversity possible and available in breeding programs. This context requires great creativity to not only maintain but to increase crop yields and ease the loss of natural resources in order to ensure global food security. Para citar este artículo Cardozo, C. (2014). Cambio climático y agrobiodiversidad. Revista colombiana de investigaciones agroindustriales, 1(1), 72-79. DOI: http://dx.doi.org/10.23850/24220582.117